VEGETATIVE PROPAGATION OF GUACO WITH ADDITION OF NAPHTALENE ACETIC ACID - COLODI, Franciely Grose; RAMOS, Nilton Luiz Ceccon; ZUFFELLATO-RIBAS, Katia Christina; RIBAS, Luciana Lopes Fortes; KOEHLER, Henrique Soares (Scientia Agraria, 2008)
The medicinal species Mikania glomerata Spr. (guaco) is native of Atlantic Forest and undergoes non-regulated extraction. Guaco’s seeds are rare, so its vegetative propagation occurs by cutting. The aim of this work was to estimate the role of naphtalene acetic acid (NAA) in root induction of M. glomerata cuttings. The experiment was installed by entire random with six treatments and four replications (10 cuttings per treatment). The treatments consisted of different NAA concentrations in powder and watersolution (0; 2500; 5000 mg kg-1 and 0; 2500; 5000 mg L-1, respectively). During August and October, 2006, cuttings were kept in a greenhouse (25 ºC ± 2 ºC, 95% RH) in Curitiba-PR. The parameters evaluated after 47 days were: cuttings survival with callus (EC); cuttings survival without callus (EV); cuttings dead (EM); cuttings rooted (EE); number of roots per cuttings (NRE); average length of the three longest roots (CRE); cuttings sprouted (BR). Death rate was low ( 3%) and 20% of cuttings sprouted. All treatments presented high roots rate ( 90%), but the powder treatment with 2500 mg kg-1 NAA showed better results for number of roots per cuttings.